Wolf Motor Function Test for Characterizing Moderate to Severe Hemiparesis in Stroke Patients - Hodics, Timea M. (2012)
OBJECTIVE: To extend the applicability of the Wolf Motor Function test (WMFT) to describe the residual functional abilities of moderate-to-severely affected stroke patients. The WMFT is a motor function test for mild to moderate upper extremity weakness in stroke patients, but it has not been routinely used for evaluation of more severe hemiparetic stroke patients due to its numerical characteristics. DESIGN: Data was collected as part of two double-blind sham controlled randomized interventional studies, the Transcranial Direct Current Stimulation (tDCS) in Chronic Stroke Recovery and tDCS Enhanced Stroke Recovery and Cortical Reorganization. Stroke patients were evaluated with the upper-extremity Fugl-Meyer (UFM) and the WMFT in the same setting prior to treatment. SETTING: University inpatient rehabilitation and outpatient clinic. PARTICIPANTS: 32 stroke patients with moderate-to-severe hemiparesis enrolled in the tDCS in Chronic Stroke Recovery and tDCS Enhanced Stroke Recovery and Cortical Reorganization studies. INTERVENTION: Not applicable. MAIN OUTCOME MEASURES: WMFT scores were calculated using 1) median performance times, 2) new calculation using the mean rate of performance. We compared the distribution of values from the two methods and examined the WMFT-UFM correlation for the traditional and the new calculation. RESULTS: WMFT rate values were more evenly distributed across their range than median WMFT time scores. The association between the WMFT rate and UFM was as good as the association between the median WMFT time scores and UFM (Spearman r(s) 0.84 vs −0.79). CONCLUSIONS: The new WMFT mean rate of performance is valid and a more sensitive measure in describing the functional activities of the moderate to severely affected upper extremity of stroke subjects and avoids the pitfalls of the median WMFT time calculations.